IMPROVING MARITIME COMMODITIES THROUGH PRODUCT DISPLAY PROGRAM AND MICROFINANCING: PENGEMBANGAN KOMODITAS BAHARI MELALUI PROGRAM DISPLAY PRODUK DAN PENDANAAN MIKRO - Prawita Yani; Muktar Redy Susila; Wawan Cahyo Nugroho; Fastha Aulia Pradhani (Faculty of Vocational Studies, Universitas Airlangga, 2026)
Background: Klampis Barat is an area on Madura Island with marine commodities as its main products. However, these commodities are mostly sold in local markets and remain in raw form due to the lack of further processing. Objective: Narrow marketing scope and a lack of processed products caused by a limited marketing network and external fund access. Supported by Bank Rakyat Indonesia (BRI) and Dinas Koperasi Usaha Kecil dan Menengah (Diskop-UKM), this program is expected to grow motivation and knowledge among Micro, Small, and Medium Enterprises (MSMEs) owners to expand their marketing network by displaying their products in Diskop-UKM gallery and proposing micro financing to develop value-added products. Method: STIESIA Surabaya team of Pengabdian kepada Masyarakat (PkM) with BRI and Diskop-UKM implemented socialization regarding requirements to display products in Diskop-UKM gallery and to propose micro financing. Results: After the activity, many participants showed enthusiasm. This result was supported by improved scores participants' questionnaire, which mostly showed improved knowledge and initiatives. Conclusion: Collaboration among entities implemented by the team of PkM has given a lot of knowledge and mutual benefit among them. Therefore, this kind of method is recommended with intensive monitoring to find out the impact on all parties.